2020
DOI: 10.1002/gj.3969
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and zircon U–Pb ages of the Neoproterozoic Shimian plutons on the western margin of the Yangtze Block, Sichuan Province

Abstract: The Shimian Neoproterozoic plutons are located on the western margin of the Yangtze Block and are important for reconstructing the tectonic environment of this region. We present in situ zircon LA–ICP–MS U–Pb geochronological and Hf isotopic analyses for the plutons, as well as whole‐rock major‐ and trace‐element compositions. The monzogranite and syenogranite yield concordant ages of 773.6 ± 5.6 Ma and 812.2 ± 1.8 Ma, respectively, which indicates that they formed during the Tonian of the Neoproterozoic. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Some scholars suggested that the Cretaceous igneous rocks in the southeast coastal formed in the back-arc extensional environment, generated by the Paleo-Pacific Plate subducted to the northwest (Xu et al, 1999;Xie et al, 2021). Others reported that the lithospheric thinning accompanied by upwelling of mantle materials, caused the melting of lithosphere and accelerated the shear action and fault zone activities (Wu et al, 2002;Li and Li, 2007).…”
Section: Dynamics Implication Of Southeast Chinamentioning
confidence: 99%
“…Some scholars suggested that the Cretaceous igneous rocks in the southeast coastal formed in the back-arc extensional environment, generated by the Paleo-Pacific Plate subducted to the northwest (Xu et al, 1999;Xie et al, 2021). Others reported that the lithospheric thinning accompanied by upwelling of mantle materials, caused the melting of lithosphere and accelerated the shear action and fault zone activities (Wu et al, 2002;Li and Li, 2007).…”
Section: Dynamics Implication Of Southeast Chinamentioning
confidence: 99%